Dieselgate As the Case of Greenwashing Practices - Ewa SNIEZEK; Michal WIATR (Communications of International Proceedings, 2022)
The Dieselgate affair spread around the world, thus becoming the largest greenwashing scandal in history, one of the most outrageous white-collar crimes and corporate scandals of recent times. This became an opportunity to discuss the problems of corporate social responsibility (CSR) and related degenerative phenomena called greenwashing. It is clear that very little attention has been placed on ‘avoiding bad’, which refers to the initiatives aimed at preventing socially irresponsible corporate practices, such as customer fraud and market manipulation. Most of the ongoing discussions on sustainability and corporate social responsibility problems in business activity has focused on good practices, which is strictly connected with the additional contributions that companies can make to the well-being of society. This emphasis has also lead to the sharp distinction between ‘talk’ and ‘do’ and to ignore the performative character that communication might have in affecting actions in business. The purpose of this paper is to present the history and consequences of the Dieselgate scandal as an example of the abuse of the concept of corporate social responsibility. This study explores the case of greenwashing behaviour. It extends the greenwashing experience by identifying a type of irresponsible behaviour – ‘deceptive manipulation’. The paper is structured as follows: first, the background and literature review for analysing the case study of greenwashing, then the case of the Dieselgate scandal. The next section comprises the discussion on Dieselgate consequences. Finally, the Volkswagen Group’s activity in order to rebuild the image of the company is shown. The paper ends with the conclusion. The research method used is a literature review and a deductive approach to case study analysis.
Keywords: greenwashing; Dieselgate; Corporate Social Responsibility; reputation demage; Volkswagen; deceptive manipulation